PROFILE UTILIZATION OF THE SCIENCE LABORATORY IN BIOLOGY LEARNING AT SMA NEGERI 1 SILANGKITANG - Erika Lusiana Tobing; Ika Chastanti; Dahrul Aman Harahap (Universitas Negeri Medan, 2021)
Biology is a science that has significant meaning for the world of education in schools. Biology can also be called a method of finding out about nature systematically, so that biology is not only a theoretical mastery of a collection of knowledge in the form of facts, concepts, or principles but also a process of finding facts with an actual process through a practicum in the Science Laboratory. The research objective was to determine the management of the Biology laboratory at SMA Negeri 1 Silangkitang. This study uses a descriptive method using a qualitative approach. The data analysis technique was carried out in a descriptive qualitative manner using the Miles and Huberman model. The results showed that the utilization of the science laboratory at SMA Negeri 1 Silangkitang was based on (1) completeness (80%); (2) Storage of tools and materials (75%); (3) Laboratory Maintenance (70%); (4) Provision of laboratories (75%; (5) Laboratory cleanliness (85%). Laboratory utilization at SMA Negeri 1 Silangkitang has been carried out well. Biology teachers carry out practicum in accordance with biology learning materials. Biology teachers attend laboratory training held in universities to develop competence in biology practicum.